1997
DOI: 10.1101/gad.11.5.558
|View full text |Cite
|
Sign up to set email alerts
|

Identification of redox/repair protein Ref-1 as a potent activator of p53.

Abstract: p53 can be isolated from cells in a form that is inert for binding to DNA but that can be stimulated dramatically by phosphorylation, antibody binding, or short single strands of DNA. This suggests that upon genotoxic stress, cells can convert latent p53 to one that is active for DNA binding. Surprisingly, we observed that latent p53 is as effective in activating transcription in vitro as is active p53. We found that HeLa nuclear extracts can stimulate DNA binding by latent p53 and have purified from them a p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
306
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(319 citation statements)
references
References 36 publications
12
306
0
1
Order By: Relevance
“…It is also likely that CAT affects the cellular redox status, leading to a modulation of gene expression through the activity of various transcription factors such as nuclear factor-kB, Fos, Jun, Myb 48 and p53. 49 Consistent with this hypothesis, it has been reported that UVB-induced ROS are involved in transcriptional activation of AP-1, 50 increased production of matrix metalloproteases 51 and also biosynthesis and activation of transforming growth factor-b. 52 We demonstrated that UVA-induced hypertrophy was decreased by the overexpression of CAT (but not by the overexpression of CuZnSOD or MnSOD).…”
Section: Discussionmentioning
confidence: 63%
“…It is also likely that CAT affects the cellular redox status, leading to a modulation of gene expression through the activity of various transcription factors such as nuclear factor-kB, Fos, Jun, Myb 48 and p53. 49 Consistent with this hypothesis, it has been reported that UVB-induced ROS are involved in transcriptional activation of AP-1, 50 increased production of matrix metalloproteases 51 and also biosynthesis and activation of transforming growth factor-b. 52 We demonstrated that UVA-induced hypertrophy was decreased by the overexpression of CAT (but not by the overexpression of CuZnSOD or MnSOD).…”
Section: Discussionmentioning
confidence: 63%
“…This activity was shown to be activated by various pathways: phosphorylation (Hupp et al, 1992), antibody speci®c for the carboxyterminus of the protein (Hupp et al, 1992), small peptides which could mimic the carboxy-terminus of the p53 (Hupp et al, 1995), short single stranded DNA (Jayaraman and Prives, 1995), deletion of the last 30 amino-acids (Hupp et al, 1992) and the interaction with a cellular protein (Jayaraman et al, 1997). In the present study, we demonstrate that this feature is not unique to Hp53, but can also be extended to Xp53.…”
Section: Discussionmentioning
confidence: 99%
“…The non speci®c binding of small oligonucleotides by the carboxy-terminal region of p53 has also been shown to activate the speci®c DNA binding activity of the central region of p53 (Jayaraman and Prives, 1995). Recently, a cellular protein, ref1, has been shown to be able to convert latent p53 to one that is active for DNA binding (Jayaraman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…via Ref1. This is proposed based on the established role of Ref1 in regulation of p53 transcriptional activities depending on the redox status and oxidized state of p53 (Jayaraman et al, 1997). Thus, a Ref1-thioredoxin complex may also participate in the regulation of p53 by ROS.…”
Section: Thioredoxin E Ects On Transcription Factorsmentioning
confidence: 99%